Emotional abuse towards children by schoolteachers in Aden Governorate, Yemen: A cross-sectional study - Ba- Saddik Amal S S; Hattab Abdullah S (BMC Public Health, 2012)
Abstract Background Emotional abuse is central to other forms of abuse. The primary objective of this paper was to estimate the prevalence of emotional abuse among pupils in basic education schools and the risk factors associated with it in Aden governorate, Yemen. Methods Four districts were randomly selected from across the governorate of Aden, 2 schools were selected at random in each district, and then 1066 pupils were randomly selected from the 8 schools. An anonymous self-administered questionnaire was used for data collection. Data were analyzed using Statistical Package for Social Sciences ver.15. Mean, standard deviation and chi square were used for descriptive statistics. Univariate and Multivariate logistic regression analysis was used to examine the associations between emotional abuse with pupils/parents characteristics. Results Pupils reported high rates of emotional abuse 55.2% at least once in their school lifetime. Male pupils had higher prevalence of emotional abuse 72.6% than females 26.1%. Teachers constituted the highest proportion of perpetrators 45.6%. Odds Ratio (95% confidence interval) showed statistically significant association between emotional abuse and pupils' gender, family type and father education: 9.94 (7.19-13.74), 1.40 (1.02-1.91), .58 (.39-.86) respectively. Conclusion Emotional child abuse was highly prevalent in pupils in basic school education. Pupils' gender, family type and father education were the main risk factors associated with emotional abuse.